PENERAPAN BAURAN PEMASARAN UNTUK MENINGKATKAN OMSET PENJUALAN PADA UD RAHMANI SASIRANGAN KABUPATEN BANJAR - Rika Sylvia; Rizki Amalia Afriana; Nor Anisa Amelia (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstract, The purpose of this study was to determine the application of the marketing mix carried out at UD Rahmani Sasirangan to increase sales turnover. The type of research used is descriptive qualitative, with sampling using incidental sampling, while the data analysis technique used is descriptive statistics.The conclusion of this study is 4P in the marketing mix applied by UD Rahmani Sasirangan, that for the product variable as many as 85 respondents (87.63%) gave a disagreeing response that the sasirangan fabric had an attractive design and motif, and as many as 88 respondents (90,72 %) give a response that does not agree with the sasirangan fabric that has good quality. For the price variable, 81 respondents (83.50%) gave a disagreeing response that the sasirangan fabric was affordable for consumers, and as many as 71 respondents (73.20%) gave a disagreeable response if buying a certain amount would be given a discount. Whereas for the location / place variables as many as 56 respondents (57.73%) responded strongly agreeing that the location / place of UD Rahmani Sasirangan was easily accessible and found, and as many as 39 respondents (39.90%) gave responses disagreeing with the size of the store owned UD Rahmani Sasirangan is quite large. And then for the promotion variable as many as 55 respondents (56.70%) gave a disagreeing response with UD Rahmani Sasirangan once advertised their products, and as many as 81 respondents (83.50%) gave disagreeing responses with UD Rahmani Sasirangan using varied media in marketing the product.